Dyslipidemias in Kidney Disease - Covic, Adrian; Kanbay, Mehmet; Lerma, Edgar V. (Springer New York : Imprint: Springer, 2014)
Dyslipidemia in chronic kidney disease is a common clinical problem and growing in prevalence.  With the recent publication of clinical practice guidelines on the management of lipid related disorders in patients affected by chronic kidney disease, an up-to-date and comprehensive resource of evidence-based literature is needed. Dyslipidemias in Kidney Disease captures the growing body of information on this subject matter. This book presents the latest clinical evidence and management guidance for patients of various demographics and stages of chronic kidney disease.  Written for the nephrologist community, as well as cardiologists and general practitioners, this guide will provide practical knowledge and fill a much needed void in the literature.  .